The Conflict Dynamics of Ahmadiyya Lombok: Public Services and Negative Stigma - Gaffar, Abdul (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2024)
The conflict of Ahmadiyya Lombok has advanced significantly since the 1980s when the fatwa of MUI (the Indonesian Ulama Council) was issued. Ahmadiyya Lombok refugees who migrated to the Transito Dormitory faced discrimination and negative stigma, as well as problems acquiring their citizenship rights, including freedom of worship based on their beliefs and limited access to public services. This study aims to answer several critical concerns, including how Ahmadiyya residents have gained access to public services since taking refuge at the Mataram Transito Dormitory, the negative stigmas they have faced, and the deviant assessments they have received. This study employs a qualitative research method using in-depth interviews with the Ahmadiyya Congregation residing at the Transito Dormitory and observations of the Transito Dormitory. The findings reveal that the Ahmadiyah Congregation faced discrimination while residing at the Transito Dormitory, characterized by limited access to public services, negative stigma stemming from heretical fatwa, and perceptions of exclusivity due to their resistance to local community preferences.